2018
DOI: 10.1038/s41467-018-06306-x
|View full text |Cite
|
Sign up to set email alerts
|

Outward open conformation of a Major Facilitator Superfamily multidrug/H+ antiporter provides insights into switching mechanism

Abstract: Multidrug resistance (MDR) poses a major challenge to medicine. A principle cause of MDR is through active efflux by MDR transporters situated in the bacterial membrane. Here we present the crystal structure of the major facilitator superfamily (MFS) drug/H+ antiporter MdfA from Escherichia coli in an outward open conformation. Comparison with the inward facing (drug binding) state shows that, in addition to the expected change in relative orientations of the N- and C-terminal lobes of the antiporter, the conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 53 publications
2
58
0
Order By: Relevance
“…Of note, the alanine substitution of Y30, which interacts with Cm but not DXC, exerted deleterious effect on the ability of E26T/D34M/A150E to confer cellular resistance against DXC. This finding may be explained by the involvement of Y30 in stabilizing the outward-facing conformation 25 . Additionally, we found that DXC reduced the ability of substrate-binding-site mutants to confer cellular resistance against Cm, regardless of whether the mutated protein residues bind DXC or Cm, thereby implying that DXC inhibits the export of Cm by E26T/D34M/ A150E, and vice versa.…”
Section: Dxc/h + Coupling In E26t/d34m/a150ementioning
confidence: 91%
See 2 more Smart Citations
“…Of note, the alanine substitution of Y30, which interacts with Cm but not DXC, exerted deleterious effect on the ability of E26T/D34M/A150E to confer cellular resistance against DXC. This finding may be explained by the involvement of Y30 in stabilizing the outward-facing conformation 25 . Additionally, we found that DXC reduced the ability of substrate-binding-site mutants to confer cellular resistance against Cm, regardless of whether the mutated protein residues bind DXC or Cm, thereby implying that DXC inhibits the export of Cm by E26T/D34M/ A150E, and vice versa.…”
Section: Dxc/h + Coupling In E26t/d34m/a150ementioning
confidence: 91%
“…1d) may occur during the substrate-induced deprotonation of A150E. The deprotonation of side-chain carboxylate of A150E, which is likely favored by the alkaline pH in the cytoplasm, may subsequently promote E26T/D34M/A150E to switch from its inward-facing state to the outward-facing conformation 25 .…”
Section: Capture Of Two Cm-binding Modes In the Crystals At The Intementioning
confidence: 99%
See 1 more Smart Citation
“…The I f crystal structure was determined from the nonfunctional mutant Q131R with bound deoxycholate and other ligands (5), while for the more recent O o structure, crystallization was facilitated by a Fab antibody fragment attached to the cytoplasmic side of the protein. (6) The solution structure of MdfA solubilized in detergent at neutral pH, was explored by double electronelectron resonance (DEER) measurements on a series of double cysteine mutants of MdfA labeled with two different spin labels -a pair of nitroxide labels (NO) or a pair of C2-Gd labels (see Fig. 1a).…”
Section: Introductionmentioning
confidence: 99%
“…Several entries have already been submitted to BSM-Arc, in various formats, sizes, and annotation styles. BSM-00001, BSM-00002, BSM-00003, BSM-00004, BSM-00006, BSM-00007, and BSM-00009 pertain to MD simulations (Bekker et al , 2019aInaba et al 2018;Oda et al 2018;Numoto et al 2018;Nagarathinam et al 2018), while BSM-00005 pertains to molecular docking (Kawabata et al 2017) and BSM-00011 and BSM-00012 to homology models (Ishizuka et al 2017;Kimura et al 2017). All the projects concerning MD simulations include representative structures, but BSM-00001 also includes all the raw trajectory data including topologies and preparation files.…”
mentioning
confidence: 99%